Efek Mediasi Kepuasan Kerja Karyawa Pada Hubungan Kepemimpinan Transformasional Dengan Komitmen Organisasi Arma Museum and Resort - Wilanda, Agung Anja (E-Jurnal Manajemen, 2014)
ABSTRACT This research was aimed at investigating the effect of transformational leadership towards the workers’ job satisfaction, the effect of transformational leadership towards the organizational commitment, the effect of workers’ job satisfaction towards the organizational commitment. The population of this research was totally 110 workers. To gain the data, interview was used as the method of data collection; meanwhile, questionnaire was used as the instrument to collect the data. Before administering the instrument, it was analyzed by means of validity testing which used factor analysis and followed by reliability testing. To analyze the gained data, simple linier regression analysis was used. Based on the data analysis, the findings were as follows: 1) there is a positive and significant effect of transformational leadership towards the workers’ job satisfaction, 2) there is a positive and significant effect of transformational leadership towards organizational commitment, and 3) there is a positive and significant effect of workers’ job satisfaction towards organizational commitment. The workers’ job satisfaction has mediated partially the relationship between transformational leadership towards the organizational commitment. Key words : transformational leadership, job satisfaction, organizational commitment Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: transformational leadership, job satisfaction, organizational commitment